1995
DOI: 10.1111/j.1440-1827.1995.tb03378.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐ras mutation of thyroid tumor with special reference to the follicular type

Abstract: Using the method of polymerase chain reaction-single strand conformation polymorphism, the point mutations of the ras oncogenes in a total of 33 thyroid tissues, including 12 follicular adenomas, 6 follicular carcinomas, 11 papillary carcinomas, and 4 undifferentiated carcinomas, were examined. The frequency of the mutation was 3% (1/33) in codon 12, 13 of Ki-ras and 18% (6/33) in codon 61 of N-ras, including 17% (2/12) in follicular adenoma, 50% (3/6) in follicular carcinoma, 0% (0/11) in papillary carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…In most cases, N-RAS and, less often, H-RAS are mutated in codon 61 (and less often in codons 12 and 13) [23,45]. In some studies, it was advanced that RAS mutations carried a guarded prognosis, but such results have not been confirmed in most series, namely when the analyses were restricted to well-differentiated carcinomas, with the exclusion of poorly differentiated and undifferentiated carcinomas [23,44].…”
Section: Follicular Carcinomamentioning
confidence: 99%
“…In most cases, N-RAS and, less often, H-RAS are mutated in codon 61 (and less often in codons 12 and 13) [23,45]. In some studies, it was advanced that RAS mutations carried a guarded prognosis, but such results have not been confirmed in most series, namely when the analyses were restricted to well-differentiated carcinomas, with the exclusion of poorly differentiated and undifferentiated carcinomas [23,44].…”
Section: Follicular Carcinomamentioning
confidence: 99%
“…In the present study, PCR-SSCP analysis was used for mutation screening [33,45]. This method has also been applied to thyroid tumours in another study [34]. In the above reports [33,34,45] neither false-negative nor false-positive re- Fig.…”
Section: Discussionmentioning
confidence: 71%
“…This method has also been applied to thyroid tumours in another study [34]. In the above reports [33,34,45] neither false-negative nor false-positive re- Fig. 2a, b Immunohistochemical demonstration of EGFR in rat thyroid tissue.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies indicated a high frequency of ras oncogene activation in thyroid carcinoma including papillary and follicular carcinomas. This ras oncogene mutation is an important event in thyroid tumor progression [20,24,29,30]. On the other hand, mutations of the ras oncogene were also reported in benign thyroid neoplasms [18].…”
Section: Discussionmentioning
confidence: 99%